Skrining Fitokimia dan Uji Antibakteri Ekstrak Daun Jambu Kristal (Psidium guajava cv. Kristal L.) - Nicolas Yonathan; Anjas, Anjas Wilapangga; Sri Royani (The Journal Of Pharmacy, 2024)
The crystal guava plant or (Psidium guajava cv. Kristal L) grows abundantly in tropical regions, especially in Kemangkon, Purbalingga, Indonesia. This plant is known for its health benefits, one of which is as an antibacterial agent due to its secondary metabolite content. This research is an experimental study that examines the secondary metabolites and antibacterial properties of crystal guava leaf extract from Kemangkon, Purbalingga. The method used is maceration extraction with 96% ethanol solvent, phytochemical screening including saponins, tannins, flavonoids, and alkaloids, and antibacterial testing using the disc diffusion method with concentrated extracts at 50 ppm and 150 ppm tested against Staphylococcus aureus, with chloramphenicol as a positive control. Phytochemical results show that crystal guava leaves contain alkaloids, flavonoids, saponins, and tannins. Antibacterial tests prove that ethanol extract of crystal guava leaves effectively inhibits bacteria, especially at concentrations of 50 ppm and 150 ppm. At 50 ppm, the inhibition zone within 24 hours reaches 1.3 cm and expands to 1.5 cm after 48 hours. At 150 ppm, the inhibition zone reaches 1.7 cm within 24 hours and remains the same after 48 hours.